Manifestations of institutional violence in the context of health care for women in situations of sexual violence - Moreira, Gracyelle Alves Remigio; Vieira, Luiza Jane Eyre de Souza; Cavalcanti, Ludmila Fontenele; Silva, Raimunda Magalhães da; Feitoza, Aline Rodrigues (Saúde e Sociedade, 2020)
The study analyzed the manifestations of institutional violence in health care for women in situations of sexual violence. This is a qualitative research based on semi-structured interviews with 68 professionals and 15 managers working in nine municipal health services in Fortaleza, Ceará, Brazil. The analysis was organized into four themes: invisibility of sexual violence; violence inwelcomingwomen; structural, drug and supply limitations; and action concerning legal abortion. The results revealed non-recognition of sexual violence as an object of intervention in the health sector and a welcome to women marked by omissions, lack of privacy, and discriminatory attitudes. Structural conditions and scarcity of drugs and supplies were mentioned as limiting for the service. Legal abortion involved cultural, managerial and institutional conflicts that favored the violation of rights. It is concluded that institutional violence in the context of care for women in situations of sexual violence goes beyond subjective issues and health professional training. And offering comprehensive care that can overcome institutional violence requires management to rethink the configuration of care network services and be close to the actors involved.